2012
DOI: 10.1007/s00038-012-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel examination of factors of the school environment and time spent in moderate to vigorous physical activity among a sample of secondary school students in grades 9–12 in Ontario, Canada

Abstract: Objective To examine associations between students' time spent in moderate to vigorous physical activity (MVPA) and the school built environment while also considering features of the schools' social environment and student-level characteristics. Methods Using surveys and GIS measures, multilevel linear regression analysis was applied to examine the environment-and student-level characteristics associated with time spent in MVPA among grade 9-12 students (n = 22,117) attending 76 secondary schools in Ontario, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 35 publications
7
50
1
4
Order By: Relevance
“…An objective measurement for PA found that students attending a school that offered daily physical education or provision of an alternative room for PA were more active than students attending a school without these resources. 12 Recent research has also shed light on specific school actions that help to support healthier behaviours. For example, students were more likely to report being active in schools that reported using activity as a reward and not as discipline, 13 those that had established community partnerships 13 and those that offered interschool PA opportunities.…”
mentioning
confidence: 99%
“…An objective measurement for PA found that students attending a school that offered daily physical education or provision of an alternative room for PA were more active than students attending a school without these resources. 12 Recent research has also shed light on specific school actions that help to support healthier behaviours. For example, students were more likely to report being active in schools that reported using activity as a reward and not as discipline, 13 those that had established community partnerships 13 and those that offered interschool PA opportunities.…”
mentioning
confidence: 99%
“…Úroveň PA ve školách pozitivně ovlivňuje vyšší počet a lepší dostupnost zařízení pro PA (De Vet, De Ridder, & De Wit, 2010;Taylor et al, 2011). Dostatečný počet dostupných sportovišť, zvýšená realizace PA o školních přestávkách, jednotkách tělesné výchovy a ve školní družině vede při dlouhodobém opakování k redukci nadváhy a obezity u dětí a může být vhodným přístupem ve snaze o zvýšení celkové úrovně PA (Haug, Torsheim, & Samdal, 2010;Hobin et al, 2012;Sigmund, El Ansari, & Sigmundová, 2012;Sigmund & Sigmundová, 2013).…”
Section: úVodunclassified
“…Z dílčích výsledků mapujících význam školního prostředí pro úroveň PA vyplývá, že kvalitní školní prostředí představuje jednu z klíčových oblastí, na kterou je nutné se zaměřit ve snaze o zvýšení úrovně PA u dětí a školáků, v prevenci dalšího nárůstu nadváhy a obezity (Hobin et al, 2012), ale také při realizaci nejrůznějších intervencí pohybového charakteru Khambalia, Dickinson, Hardy, Gill, & Baur, 2012;Lavelle, Mackay, & Pell, 2012). Z výsledků zahraničních prací také vyplývá, že mezi důležité faktory, které pozitivně ovlivňují úroveň PA dětí, patří dostatečně kvalitní zařízení a vybavení školy, především pak výukové prostředí a materiální vybavení, které by mělo vyhovovat po stránce účelové, hygienické i estetické (Gorman, Lackney, Rollings, & Huang, 2012;Gronberg, Jansen, & Taylor, 2011).…”
Section: Diskuzeunclassified
See 2 more Smart Citations